The use of NDVI derived from Pléiade images in the analysis of the vegetation structure in two forest fragments (Research, Society and Development, 2022)
The vegetation index generated through satellite images is one of the most used data in monitoring the structural parameters of vegetation in different ecosystems existing in Brazil. In this work, the characterization of the NDVI was carried out using Pléiades images with a spatial resolution of 2 meters with four spectral bands, in two forest areas corresponding to the municipality of Moju-PA whose location is 3º03`14,85409" south latitude and 48º59`36 ,15357" west longitude and another in the city of Belém-PA located at 1°26'30" S latitude and 48°27'0" W longitude. Image processing was done through the Global Mapper software. Maximum value of the NDVI for the densest vegetation reached 0.654 while the average value was 0.500 for managed forest area located in Moju-PA. In the other forest fragment located within Embrapa Amazônia Oriental, the maximum value of the NDVI indicated a reflectance value of 0.849, and the average value reached approximately 0.790. The profile of the vegetation curve generated through Pléiades images showed a positive behavior for the two forest fragments, being in the range of (0.401 to 0.654) for f forest managed from Moju-Pa and from (0.736 to 0.849) for the secondary forest of Belém-PA. Based on the observed results, it can be concluded that the NDVI, derived from Pléiades satellite images, can be used reliably in the analysis and determination of the NDVI.